Knowledge, Attitudes, and Practices toward Non-Communicable Disease Prevention in Iraqi Communities: A Cross-Sectional Study at Al-Diwaniyiah Teaching Hospital - Hamzah, Sabah Mohsin (American Journal of Biomedicine and Pharmacy, 2026)
Background: NCDs are an incredible burden on public health in Iraq and the entire MENA region and their growing rates will continue to be a significant concern in the future. The number of NCD cases continues to rise rapidly while the local community level has still not better defined KAPs concerning the prevention of NCDs. This study will assess the KAPs towards the prevention of NCDs among patients and caregivers from Al-Diwaniya Educational Hospital, examine if certain sociodemographics are contributing to lower KAP scores and to find evidence for creating targeted health promotion programs. Methods: A cross-sectional survey will take place at the Al-Diwaniyiah Teaching Hospital, Qadisiyah Governorate, Iraq from January to April of 2024. Participants will be selected from both outpatients and general medical clinics using a systematic random sampling method (420 subjects). Data will be collected via a structured interviewer-administered questionnaire that uses previously validated questions. The questionnaire will consist of 4 sections: socio-demographic characteristics; knowledge of NCDs (15); attitudes towards NCDs (10); and the practices towards NCD (12). NCD-related knowledge, attitudes and practice scores will be dichotomised into adequate and inadequate using established cut-off points for each area. The use of descriptive statistics, chi-square analysis and binary logistic regression analysis will be conducted on the data using SPSS v.26. Results: Overall, of the completed surveys, 52.4% were male and the average participant age was 38.7 (± 12.3) years. The average rate of knowledge was calculated to be 54.4% of all participants in the study. The average attitude was calculated to be 61.9% of all participants in the study, while the average rate of adequate practice was 41.7% of all participants in the study. Adequate knowledge was found to significantly correlate with sufficient education (university degree) (AOR = 3.41; 95% CI: 2.10 to 5.54), living in an urban area (AOR = 2.18; 95% CI: 1.44 to 3.31) and being a younger person (ages 18-35) (AOR = 1.87; 95% CI: 1.21 to 2.90). The areas of knowledge and the practices found to have significant deficiencies were in the domains of physical activity and dietary behaviours. There was a significant positive correlation between knowledge and attitude scores (r = 0.62, p < 0.001). Conclusion: There are major gaps in knowledge and practice related to NCDs in the Iraqi community sample, with identified deficiencies found in lower educational and rural dwellers. There is an urgent need for culturally sensitive and targeted health education programs on diet, physical activity, and smoking cessation. Al-Diwaniya Educational Hospital can be used as a community-level health promotion resource for NCD prevention.